Understanding emotions in others: mirror neuron dysfunction in children with autism spectrum disorders - Dapretto, Mirella; Davies, Mari S; Pfeifer, Jennifer H; Scott, Ashley A; Sigman, Marian; Bookheimer, Susan Y; Iacoboni, Marco (Nature neuroscience, 2006)
To examine mirror neuron abnormalities in autism, high-functioning children with autism and matched controls underwent fMRI while imitating and observing emotional expressions. Although both groups performed the tasks equally well, children with autism showed no mirror neuron activity in the inferior frontal gyrus (pars opercularis). Notably, activity in this area was inversely related to symptom severity in the social domain, suggesting that a dysfunctional 'mirror neuron system' may underlie the social deficits observed in autism.